Introducing Internet Technology to Indonesian Migrant Children at SB At-Tanzil Hicom, Malaysia: Exploring its Benefits and Challenges - Firdaus Firdaus; Andro Dewantara Noegroho; M. Sufi Ali Imran; Ari Dwi Astono; Sri Sulistiyaningsih; Martini Martini; Meizar Effendi; M. Rully Sjahirul Alim (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Indonesian migrant children in Malaysia often have limited access to digital resources, which restricts their opportunities to develop essential internet and information-literacy skills. Responding to this issue, this community service program was designed to introduce basic internet technology and promote safe, responsible, and purposeful digital use among students at SB At-Tanzil Hicom. The program aimed to strengthen their understanding of online safety, digital ethics, and the use of internet-based learning tools. A participatory approach was adopted through interactive workshops, guided practice sessions, and mentoring activities. Data were collected through observations, pre- and post-tests, and feedback from participants and teachers. The results show a clear improvement in students’ ability to navigate websites, identify credible information, and recognize online risks. Knowledge scores increased significantly, reflecting stronger digital awareness and confidence in using technology for learning. Despite challenges related to limited devices and unstable connectivity, the program effectively introduced internet literacy in a way that was accessible, contextual, and engaging for migrant learners. These outcomes highlight the importance of sustained support and collaborative efforts to ensure digital inclusion within migrant education settings.